Thermal and economical analysis of a central solar heating system with underground seasonal storage in Turkey - Ucar, A; Inalli, M (Pergamon-Elsevier Science Ltd, 2005)
Thermal performance and economic feasibility of two types of central solar heating system with seasonal storage under four climatically different Turkey locations are investigated. The effects of storage volume and collector area on the thermal performance and cost are studied for three load sizes. The simulation model of the system consisting of flat plate solar collectors, a heat pump, under ground storage tank and heating load based on a finite element analysis and finite element code ANSYS (TM) is chosen as a convenient tool. In this study, the lowest solar fraction value for Trabzon (41 degrees N) and the highest solar fraction value for Adana (37 degrees N) are obtained. Based on the economic analysis, the payback period of system is found to be about 25-35 years for Turkey. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: seasonal storage; solar energy; thermal and economical analysis